2017
DOI: 10.1007/s11096-017-0497-4
|View full text |Cite
|
Sign up to set email alerts
|

Future enhanced clinical role of pharmacists in Emergency Departments in England: multi-site observational evaluation

Abstract: Background There are concerns about maintaining appropriate clinical staffing levels in Emergency Departments. Pharmacists may be one possible solution. Objective To determine if Emergency Department attendees could be clinically managed by pharmacists with or without advanced clinical practice training. Setting Prospective 49 site cross-sectional observational study of patients attending Emergency Departments in England. Method Pharmacist data collectors identified patient attendance at their Emergency Depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 13 publications
(14 reference statements)
0
18
0
Order By: Relevance
“…It was subsequently recommended that pharmacists in the UK should manage patients with minor ailments in A&E. 12 An analysis of 18,613 A&E attendances across 49 sites in 2015 found that, with additional training, 27.9% of cases were believed to be manageable by a pharmacist prescriber. 13 In 2014, the Royal Pharmaceutical Society (RPS), based on a pilot conducted in one region within England, 14 proposed the incorporation of pharmacists into A&E in an enhanced role alongside other roles such as advanced practice nurses and physician associates. 15…”
Section: Introductionmentioning
confidence: 99%
“…It was subsequently recommended that pharmacists in the UK should manage patients with minor ailments in A&E. 12 An analysis of 18,613 A&E attendances across 49 sites in 2015 found that, with additional training, 27.9% of cases were believed to be manageable by a pharmacist prescriber. 13 In 2014, the Royal Pharmaceutical Society (RPS), based on a pilot conducted in one region within England, 14 proposed the incorporation of pharmacists into A&E in an enhanced role alongside other roles such as advanced practice nurses and physician associates. 15…”
Section: Introductionmentioning
confidence: 99%
“…The contribution and impact of the ACP role which was only partially answered by the literature. A study showed the potential contribution of ACPs being able to manage around one third of cases presenting in the Emergency Department (Hughes et al, 2017). Benefits of the role were consistent with the reasons for developing the role, which were the provision of flexible models of care where needed, across multi-professions and sectors of care.…”
Section: Impact Of the Rolementioning
confidence: 79%
“…Benefits of the role were consistent with the reasons for developing the role, which were the provision of flexible models of care where needed, across multi-professions and sectors of care. Several authors suggested ACPs were best suited within primary care roles or roles traditionally provided by primary care providers in secondary care, such as urgent care centres or a minor illness area (Barnes, Ashraf & Din, 2017;Hughes et al, 2017;Wright et al, 2018).…”
Section: Impact Of the Rolementioning
confidence: 99%
“…A patient is considered to have MetS if three out of five factors are present. 1 Purpose To critically appraise, synthesise and present the available evidence on: the types and impact of pharmacist input in MetS, to characterise the populations who would benefit most and to describe facilitators and barriers. Material and methods A search was conducted in MEDLINE, IPA, CINAHL and Cochrane using the keywords of Pharm* AND 'Metabolic syndrome*'.…”
mentioning
confidence: 99%